EU Battlegroups: What contribution to European defence? - Claudia Major; Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2011)
The EU-Battlegroups (EUBG) have been at the centre of recent debates about the Common Security and Defence Policy and its crisis response capabilities. The EU states pursued two objectives when deciding, in 2004, to set up this rapid reaction force: transformation: motivate and support EU member states to transform their armed forces in view of improving their readiness and deployability for international crisis management operations. operation. The units should enable the EU to react independently from NATO more quickly, flexibly, and thus more effectively, in different crises. This study offers the first and comprehensive evaluation of the EUBG. Overall, the EUBG turned out to be a political success, but the results in military terms are ambivalent, and the EUBG are non-existent in operational terms. They have encouraged EU states to engage with defence policy and military transformation on a permanent basis, thereby improving and intensifying EU defence cooperation. Given that the EU-Battlegroups are the only functioning EU-capability generation mechanism with a palpable outcome, they also offer some lessons with regards to the current debate on pooling and sharing of military capabilities. However, the reform effects are limited to a small portion of the national armed forces and especially to planning & command and logistics. Deficits in political decision-making processes and logistics endanger a rapid deployment. That deployments haven't yet taken place is mainly due to the different strategic cultures within the EU. The study concludes with recommendations that take into account both the results of the analysis and the security challenges ahead
Keywords: 320